2019
DOI: 10.3390/su11102877
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Spatial–Temporal Synthetic Measurement of the Coordinated Development of Population-Economy-Society-Resource-Environment (PESRE) Systems in China Based on Geographic Information Systems (GIS)

Abstract: The issue of how to realize the coordinated development of various elements in human–land systems, or, in other words, how to achieve the coordinated development of population-economy-society-resource-environment (PESRE) systems, has become an important topic, which has received global attention. This study takes 31 provinces in China as the research objects, and carries out the research on the spatial–temporal synthetic measurement of the coordinated development of PESRE systems. The conclusions are as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Based on the “3R” principle (reduce‐reuse‐recycle) of circular economy and references (Zang & Su, 2019; Lu et al, 2019; Wang, Zhao, Gong, & Ji, 2019), evaluation index system of urban system circulation level of Jinan is constructed, as shown in Table 3. Most of the data in Tables 2 and 3 are drawn from Jinan Statistical Yearbook (JMBS, 2018), and individual data are obtained through survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the “3R” principle (reduce‐reuse‐recycle) of circular economy and references (Zang & Su, 2019; Lu et al, 2019; Wang, Zhao, Gong, & Ji, 2019), evaluation index system of urban system circulation level of Jinan is constructed, as shown in Table 3. Most of the data in Tables 2 and 3 are drawn from Jinan Statistical Yearbook (JMBS, 2018), and individual data are obtained through survey.…”
Section: Methodsmentioning
confidence: 99%
“…The research process is shown in Figure 1. Based on the "3R" principle (reduce-reuse-recycle) of circular economy and references (Zang & Su, 2019;Lu et al, 2019;Wang, Zhao, Gong, & Ji, 2019), evaluation index system of urban system circulation level of Jinan is constructed, as shown in Table 3. Most of the data in Tables 2 and 3…”
Section: Corresponding Countermeasures and Suggestions Is Then Put Fomentioning
confidence: 99%
“…As for the weighting methods, existing studies could be divided into subjective weighting methods, such as the analytic hierarchy process (AHP) [4,26,27] and the Delphi method [28], objective weighting methods, such as global principal component analysis [29] and the entropy method (EM) [30][31][32][33][34][35], and combined weighting methods, such as the fuzzy analytical hierarchy process (FAHP) and the entropy method [36,37]. In general, subjective weighting methods have the advantage of considering the expert's experience while ignoring the information of the data themselves.…”
Section: Introductionmentioning
confidence: 99%
“…We chose different formulas for stimulating and non-stimulating factors [46], which take into account their specificities. where SVij represents the standardized value of xij; xij represents the actual value of the ith value in jth country; and max and min refer to the maximum and minimum value [47]. The evaluation and comparison of various indicators respecting countries to each other is an important issue in recent years [48].…”
Section: Methodsmentioning
confidence: 99%